Urgensi Aplikasi Kerangka Berpikir Computational Thinking Pada Pemebelajaran Faraid Di Era Digital - Hidayat, Yayat; Nukhbatillah, Isyfi Agni; Setiawati, Santi; Milah, Ai Robihatil; Dhiaulhaq, Fauzan; Hilma, Dede (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2023)
Computational Thinking (CT) is a method of thinking in solving problems. The research aims to elaborate on the urgency of Computational Thinking in the digital era, especially integrated in Faraid Science learning. The research method used is library research. The research results show that Computational Thinking is a solution for teachers that can be applied in schools or Islamic boarding schools. CT can stimulate students to think more logically, critically, and structuredly, and be able to solve their problems, especially at school. Computational thinking is worth trying and applying in all learning, including faraid science. Computational thinking can train students, teachers, or santri to be more critical, simple, and systematic in solving faraid science problems. Because in computational thinking there is a decomposition aspect, namely the step of simplifying a complex problem or problem, then recognizing problem patterns so you know how to solve them.